Diazinon impairs bioenergetics and induces membrane permeability transition on mitochondria isolated from rat liver - Miranda, Camila Araújo [UNESP]; Guimarães, Anilda Rufino de Jesus Santos [UNESP]; Bizerra, Paulo Francisco Veiga [UNESP]; Mingatto, Fábio Erminio [UNESP] (Taylor & Francis, 2020)
Diazinon (DZN) is a broad-spectrum insecticide extensively used to control pests in crops and animals. Several investigators demonstrated that DZN produced tissue toxicity especially to the liver. In addition, the mitochondrion was implicated in DZN-induced toxicity, but the precise role of this organelle remains to be determined. The aim of this study was thus to examine the effects of DZN (50 to 150 μM) on the bioenergetics and mitochondrial permeability transition (MPT) associated processes in isolated rat liver mitochondria. DZN inhibited state-3 respiration in mitochondria energized with glutamate plus malate, substrates of complex I, and succinate, substrate of complex II of the respiratory chain and decreased the mitochondrial membrane potential resulting in inhibition of ATP synthesis. MPT was estimated by the extent of mitochondrial swelling, in the presence of 10 µM Ca2+. DZN elicited MPT in a concentration-dependent manner, via a mechanism sensitive to cyclosporine A, EGTA, ruthenium red and N-ethylmaleimide, which was associated with mitochondrial Ca2+ efflux and cytochrome c release. DZN did not result in hydrogen peroxide accumulation or glutathione oxidation, but this insecticide oxidized endogenous NAD(P)H and protein thiol groups. Data suggest the involvement of mitochondria, via apoptosis, in the hepatic cytotoxicity attributed to DZN.
Keywords: Diazinon; liver; mitochondrial membrane permeability transition; oxidative phosphorylation; toxicity